Trend in the Incidence and Prevalence of Dementia in the Faroe Islands - Petersen, Maria Skaalum (J Alzheimers Dis, 2019)
BACKGROUND: Dementia has become an important public health, economic, and social issue. Knowledge about prevalence, incidence, and trends of dementia in a country is of crucial importance. However, no studies of incidence or prevalence of dementia have been undertaken in the Faroe Islands. OBJECTIVES: The aim was to estimate the overall and trend in incidence and prevalence of dementia among individuals ≥60 years in the Faroe Islands from 2010-2017. METHODS: Population-based register study where all individuals ≥60 years with a dementia diagnosis from January 2010 to December 2017 were identified. The overall crude and age-and-sex-specific incidence and prevalence was assessed. RESULTS: The overall crude incidence among individuals ≥60 years from 2010 to 2017 was 5.1 per 1000 individuals and the prevalence 22.5 per 1000 individuals. The age-and sex-standardized annual incidence of dementia fluctuated between 4.8 and 6.7 per 1000, with no clear secular trend while the age-and sex-standardized prevalence increased steadily from 14.5 in 2010 to 30.8 per 1000 individuals in 2017. CONCLUSION: The age-standardized incidence or prevalence estimates in the Faroes seem to be lower than in other countries. The incidence was relatively stable in the period while the prevalence of dementia simultaneously increased.